Expectations of employers in the United States for entry-level public health job skills with a bachelor’s degree: an analysis of the positions advertised in an online job portal - Kedia, Satish K.; Entwistle, Coree; Lee, Guijin; Magaña, Laura; Burke, Emily M.; Joshi, Ashish (Frontiers in Public Health, 2023)
Objectives: To analyze the current public health labor market for bachelor's-level graduates.Methods: Public health-related job postings (N = 365) from across the United States were collected from an online job portal, Indeed.com, from November 7-14, 2022. Job titles, organization type, degree requirements, work experience, job location, and preferred skills for bachelor's-level public health positions were analyzed.Results: Thirty-one job titles were identified. Approximately one-third (32.33%) of postings were from the Northeastern US; 23.56% were from the Southeastern region. Thirty-five job skill categories were identified. Most jobs (92.33%) required oral and written communication skills, and 85.21% specified educational skills for public health promotion. Cultural competency, project management, and case management abilities were also highly sought.Conclusions: This study revealed the needs of the public health workforce and bolstered the case that public health degree-seekers should be equipped with a set of strategic skills applicable to a range of multisectoral and multidisciplinary public health jobs.Policy Implications: Given the rapid changes in the field of public health, ongoing analysis of the labor market benefits educators, employers, and policymakers alike.